2015
DOI: 10.3126/jcmc.v4i3.11931
|View full text |Cite
|
Sign up to set email alerts
|

A clinical approach to ocular myasthenia gravis

Abstract: Myasthenia gravis is a common disorder of the neuromuscular junction characterized clinically by muscle weakness and fatigability. Ocular myasthenia is often misdiagnosed in the initial stages due to the fluctuating nature of ptosis and diplopia. Here, we describe the clinical characteristics of ocular myasthenia gravis along with the diagnostic difficulties in a tertiary eye care center in Nepal. We retrospectively reviewed the charts of the patients diagnosed as ocular myasthenia gravis in Neuro-ophthalmolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…A previous Nepalese study among ocular myasthenia patients has shown that 20% of patients were found to have AChR antibody positive, 75% were ice pack test positive and 83.3% had neostigmine test positive. 22 In this study, we will classify the clinical subtypes and understand the clinical manifestations along with serological and electrophysiological fi ndings.…”
mentioning
confidence: 99%
“…A previous Nepalese study among ocular myasthenia patients has shown that 20% of patients were found to have AChR antibody positive, 75% were ice pack test positive and 83.3% had neostigmine test positive. 22 In this study, we will classify the clinical subtypes and understand the clinical manifestations along with serological and electrophysiological fi ndings.…”
mentioning
confidence: 99%